European economic integration and the export behaviour of firms - Harald Trabold (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper explores the mechanisms by which economic integration leads to increased trade between new and old member states of the EC. Theoretical considerations imply that the increase in the export value should, to a large extent, be due to new exporters entering new markets. Moreover, small firms should experience a stronger rate of entry than medium and large-scale firms. Empirical evidence using enterprise related trade data for more than 20,000 French firms is presented which confirms the theoretical considerations.
Keywords: D21; F15; 330; European economic integration; export behaviour of firms; small-scale exporters